Calculating Reproductive Performance in Beef Operations: The University of Florida Beef Herds' 2019 Breeding Season - Mario Binelli; Angela Maria Gonella-Diaza; Thiago Martins; Cecilia C. Rocha; Felipe A.C.C. Silva; Federico Tarnonsky; Sergio Roskopf; Owen D. Rae; Danny Driver; Nicolas DiLorenzo; Jose Dubeux; David Thomas (EDIS)
This publication reviews the basic calculations of reproductive performance and reports the reproductive performance of two University of Florida beef herds. Written by Mario Binelli, Angela M. Gonella-Diaza, Thiago Martins, Cecilia C. Rocha, Felipe A. C. C. Silva, Federico Tarnonsky, Sergio Roskopf, Owen Rae, Danny Driver, Nicolas DiLorenzo, Jose Dubeux, and David Thomas, and published by the UF/IFAS Department of Animal Sciences, May 2021.